Penyelesaian Sengketa Proses Pemilu Oleh Bawaslu, Tantangan Dan Masa Depan - Aermadepa Aermadepa (Universitas Muhammadiyah Tapanuli Selatan, 2019)
This paper aims to discuss dispute resolution of Election process by Election Supervisory Agency (Bawaslu), as well as challenges and how to dispute the election process in the future. Act Number 7 of 2017, Article 95 letter d authorized the Election Supervisory Agency to receive, examine, mediate and adjudicate and decide on the resolution of election disputes. This means that based on Act Number 7 of 2017 in resolving disputes over the election process, Bawaslu is given additional authority to conduct mediation and adjudication. Settlement of disputes by Bawaslu is a crown whose existence is awaited by the community in resolving disputes that often occur during the election stage. To answer the challenge and to get to the destination someday Bawaslu becomes the Election Court, then Bawaslu must immediately build facilities to maintain the effectiveness and capacity of Regional Bawaslu, especially District / City Bawaslu to bemore active in training their abilities and their mentaly, which are still low in resolving election disputes.Key words: Dispute resolution, General election, Election Supervisory Agency.